Factors Influencing the Use of Premature Baby Development Monitoring with Denver II by Posyandu Cadres - Zakiyyah, Muthmainnah; Ekasari, Tutik (Mulawarman International Conference on Tropical Public Health, 2025)
Background : The prevalence of premature babies in Indonesia is still relative high, namely 7-14%, and in some districts it even reaches 16%. This prevalence is greater than in several developing countries, namely 5-9%. The national prevalence of LBW is 11,5%. Objective : The aim of this research is to determine the factors that most influence the use of monitoring the development of premature babies with Denver II by posyandu cadres in Probolinggo Regency. Research Methods/ Implementation Methods : . This research is an analytical research with a cross sectional research design. Population : all posyandu cadres are 6.645 people. Sampling uses simple random sampling. The sample consisted of 376 posyandu cadres. Data analysis uses logistic regression. Results : The results of the research are that there is an influence of knowledge, attitudes and practices of posyandu cadres on the use of monitoring the development of prematur babies wtih Denver II. The dominant factor influencing the use of monitoring the development of premature babies with Denver II is the attitude of posyandu cadres. Conclusion/Lesson Learned : Efforts that can be made are that health workers provide education to posyandu cadres so that they can monitor the development of prematur babies using Denver II.